VLSI-SoC: Technologies for Systems Integration 17th IFIP WG 10.5/IEEE International Conference on Very Large Scale Integration, VLSI-SoC 2009, Florianópolis, Brazil, October 12-14, 2009, revised selected papers - IFIP TC10/WG10.5 International Conference on Very Large Scale Integration of Systems-on-Chip Florianópolis, Brazil) 2009; Becker, Jurgen; De Oliveira Johann, Marce; Reis, Ricar; SpringerLink (Online service). (Heidelberg New York Springer, 2011)
This book contains extended and revised versions of the best papers presented at the 17th IFIP WG 10.5/IEEE International Conference on Very Large Scale Integration, VLSI-SoC 2009, held in Florianópolis, Brazil, in October 2009. The 8 papers included in the book together with two keynote talks were carefully reviewed and selected from 27 papers presented at the conference. The papers cover a wide variety of excellence in VLSI technology and advanced research addressing the current trend toward increasing chip integration and technology process advancements bringing about stimulating new challenges both at the physical and system-design levels, as well as in the test of theses system
Electronic reproduction.
Keywords: Integrated circuits -- Very large scale integration -- Congresses; Systems on a chip -- Congresses; Systems integration -- Congresses; Electronic books